Safety Evaluation in Healthy Colombian Volunteers of P2Et Extract Obtained from Caesalpinia spinosa: Design 3+3 Phase I Clinical Trial. (23rd February 2022) - Duran, María I; Ballesteros-Ramírez, Ricardo; Tellez, Angélica; Torregrosa, Lilian; Olejua, Peter A; Galvis, Silvia; Urueña, Claudia; Fiorentino, Susana
Abstract : The polyphenol-enriched extract called P2Et derived from Caesalpinia spinosa (C. spinosa) had antitumor and immunomodulatory activities reported in breast cancer, leukemia, and melanoma. The aim of this study was to evaluate the safety and maximum tolerated dose of P2Et extract in Colombian healthy volunteers in a phase 1 clinical trial, open labelled, single-arm, dose-escalation design 3 + 3. Seven healthy volunteers were included; P2Et was administrated in capsules of 600 mg/d for 28 days. Analysis by intention to treat was performed. 4 volunteers showed adverse events and discontinued the intervention. 94.6% of AE were grade 1, and most of AE had a reasonable possibility of a relationship with the P2Et (83.8%). We found that the oral administration of P2Et is safe in healthy humans with a maximum tolerated dose of 600 mg/d. There was no severe toxicity; most of the adverse events were mild, without significant changes in the safety parameters evaluated.